Mechanistic study on the mitigation of cadmium accumulation in Ligusticum sinense cv. Chuanxiong through plant growth-promoting rhizobacteria Arthrobacter sp. CX-2 - Shu-qi Niu; Ting Li; Lin Liu; Xiu-wen Bao; Xing-mao Yang; Hao-ran Song; Yang Li; Jing Bai; Li-ying He; Qing-he Wang; Si-jing Liu; Jin-lin Guo (Plant Stress)
Ligusticum sinense cv. Chuanxiong is commonly used in traditional Chinese medicine (TCM) to promote blood circulation, dispel wind, and relieve pain. However, the accumulation of cadmium (Cd) in L. Chuanxiong and Cd pollution in its genuine producing areas have resulted in significant concerns about excessive Cd levels in these medicinal materials. In this study, Arthrobacter sp. CX-2, a plant growth-promoting rhizobacteria (PGPR) strain from L. Chuanxiong rhizosphere soil, could promote growth and decrease Cd accumulation of L. Chuanxiong in the field. Inoculation CX-2 significantly increased the dry weight of rhizome (36.98 %), meanwhile decreased the Cd content in leaves (20.50 %) and rhizomes (33.23 %). Specifically, CX-2 could markedly reduce Cd transportation capacity of L. Chuanxiong, such as the translocation factor (TF) Leaf/root (30.66 %) and TF rhizome/root (41.66 %). Above all, as a TCM, the pharmacological effects of L. Chuanxiong were not affected by the addition of CX-2, which was confirmed through cell experiments. For rhizosphere soil, CX-2 significantly decreased the exchangeable Cd content by 36.84 % and enhanced the availability of nutrients. Metagenome analysis demonstrated that the structure, composition, and function of the rhizosphere microbial community significantly changed in the CX-2 group. There were 24 dominant differential microorganisms in the CK group and 29 in the CX-2 group. Among them, Nitrospirae, Acidobacteria, and Gemmatimonadaceae dominated in the CX-2 group. In addition, regulation of Carbohydrate metabolism, Energy metabolism, and Xenobiotics biodegradation and metabolism pathways by CX-2 in rhizosphere microorganisms might ultimately lead to a change in Cd accumulation of L. Chuanxiong. To our knowledge, this is the first study to explore the application of PGPR from the rhizosphere of L. Chuanxiong in the field environment, promoting its growth and reducing its Cd content. This work provides insights into using PGPR and offers a promising biotechnological approach to solve Cd accumulation in medical plants.